Maternity benefits mandate and women's choice of work in Viet Nam - Khoa Vu; Paul Glewwe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Despite a sizeable literature on the labour market effects of maternity leave regulations on women in developed countries, how these policies affect women's work in developing countries with a large informal sector remains poorly understood. This study examines how extending the maternity leave requirement affects women's decisions to work in the informal or formal sector in Viet Nam. We use a difference-in-differences approach to evaluate the 2012 Amendment to the Viet Nam Labour Law, which imposes a longer maternity leave requirement than before. We find that the law increases formal employment and decreases unpaid work among women in the female labour market. This is driven by women switching from agricultural household work to employment in the public sector. In contrast, we find no effects on formal employment in the private sector. These findings suggest that an increase in the required maternity leave encourages women to switch from informal, unpaid work to working in the formal sector.
Keywords: J08; J2; J3; 330; maternity leave regulations; female labour market; informal sector